Healing developmental trauma : how early trauma affects self-regulation, self-image, and the capacity for relationship - Heller, Laurence, 1944-; LaPierre, Aline, 1944- (North Atlantic Books, 2012)
"Written for those working to heal developmental trauma and seeking new tools for self-awareness and growth, this book focuses on conflicts surrounding the capacity for connection and introduces the NeuroAffective Relational Model, a unified approach to developmental, attachment, and shock trauma"--Provided by publisher.
Keywords: neuropsychologie; psychická traumata; emoční poruchy v dětství a dospívání; psychoterapie; neuropsychology; psychic trauma; emotional disorders in childhood and adolescence; psychotherapy; monografie; monographs